I'm having 2 problems at finding the correct interval of convergence of this power series.

$$\sum_{n=1}^∞ \frac{n(x-3)^{2n+1}}{2^{n}-1}$$

What I did was use the good old Ratio Test:

$\lim\limits_{n \to ∞} \left\lvert\frac{(n+1)(x-3)^{2n+3}}{2^{n+1}-1}*\frac{2^{n}-1}{n(x-3)^{2n+1}}\right\rvert$

Simplyfying the expression I got:

$\lim\limits_{n \to ∞} \left\lvert\frac{n+1}{n}*\frac{2^{n}-1}{2^{n+1}-1}*(x-3)^{2}\right\rvert$

The first limit equals $1$ and the second one equals $1/2$ so I get:

$\lim\limits_{n \to ∞} \left\lvert 1*\frac{1}{2}*(x-3)^{2}\right\rvert$=$\left\lvert\ \frac{(x-3)^{2}}{2}\right\rvert$

Since I want the Interval of $convergence$, my limit must be less than $1$:

$\left\lvert\ \frac{(x-3)^{2}}{2}\right\rvert$<$1$

Now here is the first problem, If I solve this, I get:





The lower value of the interval is not a real number at all, how do I evaluate this?.

The second problem comes when I evaluate the upper value of the interval $x=\sqrt{2}+3$. This is the Series that I obtain:

$$\sum_{n=1}^∞ \frac{n(\sqrt{2}+3-3)^{2n+1}}{2^{n}-1}$$

$$\sum_{n=1}^∞ \frac{n(\sqrt{2})^{2n+1}}{2^{n}-1}$$

$$\sum_{n=1}^∞ \frac{n(2^{1/2})^{2n+1}}{2^{n}-1}$$

$$\sum_{n=1}^∞ \frac{n(2)^{n+1/2}}{2^{n}-1}$$

I look at this Series and I just can't tell if it converges or diverges, It doesn't look like anything I did before.

So, basically that's it, I can't tell what happens with the lower value of the interval of convergence and I can't find a way to prove the Power series at $x=\sqrt{2}+3$ is Convergent or Divergent.

Hope it wasn't too long, I wanted to show everything I did.

Thank you for any help.


Following your steps, the convergence is ensured for all real numbers $x$ such that $$ (x-3)^2<2 \iff |x-3|<\sqrt{2} \iff 3-\sqrt{2}<x<3+\sqrt{2}. $$

  • By putting $x=3+\sqrt{2}$ into the series one has $$ \sum_{n=1}^∞ \frac{n(x-3)^{2n+1}}{2^{n}-1}=\sqrt{2}\cdot\sum_{n=1}^∞ \frac{n\cdot2^{n}}{2^{n}-1} $$ the latter series does not converge since $$ \lim_{n \to \infty}\frac{n\cdot2^{n}}{2^{n}-1}=\infty\ne0. $$
  • By putting $x=3-\sqrt{2}$ into the series one has $$ \sum_{n=1}^∞ \frac{n(x-3)^{2n+1}}{2^{n}-1}=-\sqrt{2}\cdot\sum_{n=1}^∞ \frac{n\cdot2^{n}}{2^{n}-1} $$ which does not converge as seen previously.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.